Therapeutic importance of hydrogen sulfide in cognitive impairment diseases - Wei, Hai-Jun; Tan, Hui-Ying; Cao, Jian-Ping; He, Juan; Zhang, Qing-Li; Jiang, Li; Zhou, Gui-Juan; Xiao, Fan (Brain research, 2025)
[Display omitted] •H2S, synthesized by brain enzymes, functions as a neuromodulator with antioxidant and neuroprotective properties.•Lower H2S levels in cognitive disorders highlight its key role in learning and memory regulation.•Preclinical studies show H2S improves cognition in neurodegenerative, vascular, trauma, diabetes models.•This review supports for H2S's potential as a novel therapeutic approach in treating cognitive disorders. The brain naturally synthesizes hydrogen sulfide (H2S) via enzymes such as cystathionine-β-synthase (CBS), 3-mercaptopyruvate sulfurtransferase (3-MST), cysteine aminotransferase (CAT), and cystathionine-γ-lyase (CSE). From a physiological point of view, H2S serves as a neuromodulator with antioxidant and neuroprotective properties. Recent research suggests that H2S is crucial in regulating learning and memory, as its downregulation is commonly observed in cognitive impairment diseases. Preclinical studies suggest that external supplementation, through donors like sodium hydrosulfide (NaHS), can improve cognitive impairment in various cognitive disorder models. Moreover, numerous molecular mechanisms have been proposed to explain the effects of these H2S donors. This review aims to detail the roles of H2S in various models of cognitive impairment and in human subjects, highlighting its potential mechanisms and providing experimental support for its use as a novel therapeutic approach in treating cognitive disorders. Overall, H2S plays a significant role in the treatment of cognitive impairment diseases, but further large-scale studies are still required to support the results of current research.